Complete Guide to Microsoft Copilot for Security: Empower and Protect the Security Operations Center (SOC) by Microsoft Press. - Snyder, Eric; Muniz, Joseph; Press, Microsoft (linkedin.com, 2024)
Get started with the comprehensive AI-powered security solution: Microsoft Copilot for Security.